Assessing Occupational Hazards for Tiling Works at Construction Site - Mohd Nizam, Muhammad Aiman Syahmi; Zuritah A Kadir; Zulfazly Zaini (Progress in Engineering Application and Technology, 2025)
Occupational hazards in construction are a significant concern, especially for specialized tasks such as tiling, where workers face several risks. These hazards frequently arise from the physically intensive nature of the labor, the utilization of hazardous substances, and the unstable conditions of construction sites. This study seeks to carefully evaluate the occupational hazards linked to tiling work, emphasizing the identification of potential hazards, performing risk assessment and recommending appropriate control measures for mitigating hazards. The study used a mixed-approaches approach, integrating both quantitative and qualitative methods for gathering data such as field observations, hazard identification techniques, and systematic interviews with construction employees and executives that were performed at several locations at construction site. The research additionally encompasses an evaluation of safety protocols and adherence to current occupational safety and health regulations. Significant data indicates that tiling workers often encounter physical hazards, such as fall from height, exposure to sharp tools and machinery, and injuries resulting from slips, trips, and falls. Chemical hazards are considerable, as employees frequently manage adhesives, grout, and cleaning solvents without sufficient personal protective equipment (PPE), resulting in skin irritation and respiratory problems. Moreover, inadequacies in safety training, insufficient implementation of safety protocols, and an absence of ergonomic gear enhance the total potential hazards for tiling workers. This research offers a comprehensive review of the occupational hazards encountered by tiling workers and suggests practical solutions, thereby enhancing safety standards within the construction sector.